Urolithiasis Problems in Finishing Pigs - Joris Vrielinck; Geert P. J. Janssens; Ilias Chantziaras; An Cools; Dominiek Maes (Veterinary Sciences, 2023)
This paper describes cases of urolithiasis in fattening pigs on two farms (A and B). Bladder rupture due to urethral obstruction with calculi was the principal finding during the necropsy of the pigs. An in-depth diagnostic examination was performed to elucidate possible pathophysiological mechanisms, namely Fourier-transform infrared spectrophotometry (FT-IR) analysis of the uroliths, blood analysis (farm A: 5 samples, farm B: 10 samples) for assessing concentrations of minerals, the bone resorption marker cross-linked C-telopeptide of type 1 collagen (CTX), parathyroid hormone (PTH), and vitamin D components, biochemical urinalysis (farm A: 5 samples, farm B: 7 samples), microscopic examination of urinary sediment (Farms A and B: 7 samples each), mineral composition of the feed, and analysis of the drinking water. Calcium carbonate was the main component found in stones from both farms, and calcium carbonate and struvite were the main components found in crystals from farms A and B, respectively. On farm A, urinary calcium excretion and urinary pH were high; on farm B, urinary phosphorus was high and urinary calcium was low with a normal urinary pH. The mineral compositions of the feed and drinking water were similar on both farms and could therefore not explain the difference between the two farms. Disturbances in calcium and phosphorus absorption and homeostasis might have been involved in these problems. Further research should focus on the calcium, phosphorus, and vitamin D levels in the feed and take into account other factors, such as the absorption and excretion of minerals due to gut and urinary microbiota.